PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR SISWA KELAS VII SMP NEGERI 12 PADANG - Tressyalina, Maretta Arviyana Syahrul R., (Universitas Negeri Padang, 2017)
The purpose of this study were (1) to describe the skills of writing the text of the procedures of the students of class VII of SMP Negeri 12 Padang without using the audiovisual media aided discovery learning model. (2) to describe the skills of writing the text of the procedure of class VII students of SMP Negeri 12 Padang by using discovery learning model audiovisual media. (3) to analyze the effect of audiovisual media aided discovery learning model to the writing skills skill of class VII students of SMP Negeri 12 Padang. Based on data analysis, the use of audiovisual media-aided discovery learning model influences the writing skills skill of class VII students of SMP Negeri 12 Padang.Â Kata Kunci: pengaruh, discovery learning, media audiovisual, menulis teks prosedur